2021
DOI: 10.2166/ws.2021.193
|View full text |Cite
|
Sign up to set email alerts
|

Predicting relative energy dissipation for vertical drops equipped with a horizontal screen using soft computing techniques

Abstract: This study was designed to evaluate the ability of Artificial Intelligence (AI) methods including ANN, ANFIS, GRNN, SVM, GP, LR, and MLR to predict the relative energy dissipation(ΔE/Eu) for vertical drops equipped with a horizontal screen. For this study, 108 experiments were carried out to investigate energy dissipation. In the experiments, the discharge rate, drop height, and porosity of the screens were varied. Parameters yc/h, yd/yc, and p were input variables, and ΔE/Eu was the output variable. The effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 31 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Sihag et al, (2019) used ANFIS, SVM and random forest (RF) for the prediction of cumulative infiltration (CI) and infiltration rate (IR) in arid areas in Iran. Norouzi et al, (2021) applied ANN, ANFIS, generalized neural network (GRNN), SVM, GP, LR, and multiple linear regression MLR to predict the relative energy dissipation for vertical drops equipped with a horizontal screen and found that the performance of ANFIS model was outperforming among other applied models. The performance of SVM based model was better than ANFIS and RF based model for the prediction of CI and IR.…”
Section: Introductionmentioning
confidence: 99%
“…Sihag et al, (2019) used ANFIS, SVM and random forest (RF) for the prediction of cumulative infiltration (CI) and infiltration rate (IR) in arid areas in Iran. Norouzi et al, (2021) applied ANN, ANFIS, generalized neural network (GRNN), SVM, GP, LR, and multiple linear regression MLR to predict the relative energy dissipation for vertical drops equipped with a horizontal screen and found that the performance of ANFIS model was outperforming among other applied models. The performance of SVM based model was better than ANFIS and RF based model for the prediction of CI and IR.…”
Section: Introductionmentioning
confidence: 99%